Dickinson's Fascicles : A Spectrum of Possibilities - Crumbley, Paul, 1952-; Heginbotham, Eleanor Elson; Project Muse. (Columbus : Ohio State University Press, 2014)
"In this volume, a number of senior and emerging Dickinson scholars raise their disparate voices with a particular set of theoretical premises, each selecting specific fascicles for close inspection. The result is the first practical, balanced, common ground for studying Dickinson's poetry in her own context"--
Description based on print version record.
Keywords: Dickinson, Emily, -- 1830-1886.; Dickinson, Emily, -- 1830-1886 -- Criticism, Textual; Dickinson, Emily, -- 1830-1886 -- Manuscripts; Dickinson, Emily, -- 1830-1886 -- Criticism, Textual; Dickinson, Emily, -- 1830-1886 -- Manuscripts; LITERARY CRITICISM -- Poetry; Dickinson, Emily, -- 1830-1886 -- Technique; Manuscripts; Criticism, interpretation, etc; Electronic books